REALITAS KOMPETENSI GURU PASCA SERTIFIKASI - Fitria Nur Anggranei (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
The world of education in Indonesia cannot be proud of itself, many international reports show the level of education in the middle category (for example UNDP & GTCI). In fact, this concern is bigger when looking at the facts on the ground, how many problems and shortages in Indonesian education are, and the most terrible thing is the quality of the teaching force. This study seeks to show evidence, how to portray the competence of educators in Indonesia. Can a certification program increase the knowledge and abilities of educators? This is the main topic of research. So that we can see, to what extent are the roles of the government, the ministry of education, the schools, and the teachers themselves, trying to improve their professionalism, so as to make a real contribution to realizing a smart and prosperous society. To that end, a qualitative approach was taken. Namely, a research process that uses an empirical approach, in order to reveal the real situation. The results showed that the certification program was not interpreted as an effort to increase competence, but rather to improve welfare